2017
DOI: 10.1111/jav.01402
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐functional crest display in hoopoes Upupa epops

Abstract: Animals can engage in visual displays, which may target conspecifics, heterospecifics or both. Here we studied the function of the flamboyant crest‐raising display of hoopoes Upupa epops in experiments performed with males in captivity. Males were exposed to sounds of a conspecific (male hoopoe song), a potential predator (human voice), and two controls (the song of a blackbird Turdus merula, and background noise). These stimuli were presented to males in the presence and absence of females. Males raised the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
0
1
2
Order By: Relevance
“…In crested birds, crest rising is well described as being involved in body threat displays or sexual displays (e.g. [ 21 , 30 , 31 ]); however, in our study, no agonistic interactions were observed between parrots, and birds were non-breeding juveniles (no expression of sexual displays). The high proportion of scans with nape ruffling during low arousal levels is also consistent with observations in passerine birds.…”
Section: Discussioncontrasting
confidence: 84%
“…In crested birds, crest rising is well described as being involved in body threat displays or sexual displays (e.g. [ 21 , 30 , 31 ]); however, in our study, no agonistic interactions were observed between parrots, and birds were non-breeding juveniles (no expression of sexual displays). The high proportion of scans with nape ruffling during low arousal levels is also consistent with observations in passerine birds.…”
Section: Discussioncontrasting
confidence: 84%
“…Burung Hud-Hud (Upupa epops) beraktivitas dilahan terbuka dengan kondisi yang lembap dan memiliki kemampuan yang bagus berupa insting yang luar biasa, memiliki penglihatan yang dapat menjangkau sesuatu di balik keterbatasan mata memandang, memiliki kecerdasan dalam memahami serta merespon hal-hal yang terjadi di lingkungan sekitarnya. Oleh karena itu, kelebihan yang dimiliki oleh burung ini dijadikan sebagai alat yang dapat mengkomunikasikan misi kenabian dan kerasulan Nabi Sulaiman dengan individu yang menjadi tujuannya [4].…”
Section: Pendahuluanunclassified
“…Sedangkan Burung Hud-Hud yang masih kecil, mereka memiliki metode pertahanan mereka sendiri. Ketika merasa terancam mereka akan menyemprotkan kotorannya tepat ke wajah predator itu untuk mempertahankan diri [4]. E. Perilaku Komunikasi Gambar 3.4 Perilaku komunikasi Burung Hud-Hud (Upupa epops) Interaksi sosial pada Burung Hud-Hud (Upupa epops) melibatkan berbagai bentuk komunikasi antara sesama jenis dan lingkungan sekitarnya.…”
Section: Perilaku Burung Hud-hud (Upupa Epops) Dalam Perspektif Sainsunclassified